Understanding a child the occupational therapy way : recognizing and communicating the unique potential of a child - Adair, Sabrina E. (New York, NY : Routledge, 2022)
'This book outlines an occupational therapy perspective to observing, understanding, and giving a voice to children who have difficulty communicating. Using a biopsychosocial approach, the book explains how and why a child may think, feel, and act based on environmental and social influences and sensory and learning needs. Presented in accessible, everyday language, chapters help readers identify, describe, and clearly articulate the child's environment, the way that they process different sensory inputs, and how they learn. By treating children holistically and effectively communicating their story to others, the reader can identify the most effective ways to set up an environment to meet a child's needs and set them up for success. Therapists, educators, parents, and childcare workers will all benefit from the simple strategies outlined in this book to enrich a child's learning and maximize their potential'--
Introduction -- Occupational therapy -- Understanding the caregiver -- Understanding the child -- Acknowledging the sensory world -- Understanding how children learn -- Understanding behaviors -- Helping a child find balance -- Integrating into the environment -- Influence of family/caregiver support -- Collaborative problem solving -- Communication with the school -- Communication with health care providers -- Conclusion.
Includes bibliographical references and index.
Online resource; title from digital title page (ProQuest Ebook Central, viewed October 27, 2021).
Sabrina E. Adair, MScOT, is a practicing occupational therapist, a mom to four unique and beautiful children, and a passionate advocate for parent empowerment.
WorldCat record variable field(s) change: 650
Keywords: Occupational therapy for children; Occupational therapy; Occupational Therapy; EDUCATION / Special Education / Learning Disabled; PSYCHOLOGY / Psychopathology / Autism; Occupational therapy for children; Electronic books